2017
DOI: 10.1080/13614533.2017.1365735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brief Integrated Information Literacy Education Sessions on Undergraduate Engineering Students' Interdisciplinary Research

Abstract: Engineering students often conduct information searches without sufficient consideration of the context of their research topic. This article discusses how development of a new information literacy (IL) mindset through instruction in integrated IL education affects students' understanding of research problems and formulation of information search questions. The course observed is a mechanical engineering seminar for undergraduate engineering students with integrated IL education. A survey-based research method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…A seminar report of the American Library Association (ALA) in 1989 stated that in order to be able to produce the information literate society, the thing to do is to integrate the concept of information technology as a program in learning activities of the schools and colleges [9]. In order to realize the integration of information technology and learning activities there should be some efforts of the teachers and librarians.…”
Section: B Information Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…A seminar report of the American Library Association (ALA) in 1989 stated that in order to be able to produce the information literate society, the thing to do is to integrate the concept of information technology as a program in learning activities of the schools and colleges [9]. In order to realize the integration of information technology and learning activities there should be some efforts of the teachers and librarians.…”
Section: B Information Literacymentioning
confidence: 99%
“…The reason they use the tools of information retrieval for reasons already accustomed to using search engines are known for. A person can be said to be information literate if he can use a search engine with consideration of the understanding and the knowledge they have about the search engine [9].…”
Section: E Pupils As Pioneersmentioning
confidence: 99%
“…However, the curriculum does not specifically focus on information literacy or question formulation. Yet, as in our experience with FED101, other engineering educators have found that students are still lacking the logical and critical thinking skills that are required to develop a compelling inquiry of a topic, and have difficulty performing effective information searches [14,16]. Teaching students how to formulate research questions not only helps them in the research process but also develops the skill of using their curiosity to drive their inquiry, a skill essential in engineering [17].…”
mentioning
confidence: 87%
“…First-year students in particular have demonstrated improved skills in information literacy when library sessions are incorporated into their curriculum [13]. Library instruction can help to create a "supportive learning environment" in which first-year students are both challenged and supported through the transition to university-level work, leading to more positive outcomes as they progress through their degree program [14].…”
Section: Literature Reviewmentioning
confidence: 99%